Mander’s Reagent for the Deoxycyanation of β-Diketones: A Direct Synthesis of Oxoalkenenitriles - Cruz-Jiménez, Alicia E.; Mateus-Ruiz, Jeferson B.; Silva-Cuevas, Carolina; Lujan-Montelongo, J. Armando (Synlett, 2022)
Ethyl cyanoformate and methyl cyanoformate (Mander’s reagent) are both routinely used to perform C-selective ketone alkoxycarbonylations. Interestingly, both reagents were found to yield oxoalkenenitriles through an unprecedented deoxycyanation of 1,3-dicarbonyl compounds (e.g., 2-methylcyclohexane-1,3-dione). Although this method is not general, this is the first time that both Mander’s reagent and ethyl cyanoformate have been used for the deoxycyanation of 1,3-dicarbonyl compounds for the preparation of synthetically useful oxoalkenenitriles. Limitations on the substrate scope of the present method are discussed.
Keywords: Mander’s reagent; alkyl cyanoformates; deoxycyanation; oxoalkenenitriles; β-diketones